Image Fiber-Based Miniature Suspended Solid Sensor with High Accuracy and a Large Dynamic Range. Issue 1 (December 2017) - Qi, Pengfei; Lin, Lie; Huang, Rui; Zhao, Sicong; Tian, Haolin; Li, Shuai; Zhang, Qinghe; Liu, Weiwei
Abstract An image fiber-based miniature suspended solid sensor has been demonstrated. The diameter of the sensor is only a few millimeters. A superhydrophobic material is coated on the end of the image fiber to avoid the adsorption of suspended solids and bubbles. Multiple parameters, including mass concentration, morphology and particle sizes of suspended solids, can be visually measured in real time. Dynamic ranges of 0 ~100 kg/m3, full range accuracies of ±2‰ and a response time of 0.05 s were experimentally realized for the mass concentration measurements. Determinations of particle sizes of the suspended solids are also presented by means of digital image processing. This new technique will significantly advance ultralow-intrusion measurements in studies on the dynamics of suspended solids.